2022
DOI: 10.3390/polym14071301
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cycle Fatigue Behavior of 3D-Printed PLA Reinforced with Natural Filler

Abstract: Additive production is currently perceived as an advanced technology, where intensive research is carried out in two basic directions—modifications of existing printing materials and the evaluation of mechanical properties depending on individual production parameters and the technology used. The current research is focused on the evaluation of the fatigue behavior of 3D-printed test specimens made of pure PLA and PLA reinforced with filler based on pinewood, bamboo, and cork using FDM (fused deposition modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…[ 153 , 154 ]. Previously, most research focused on synthetic fiber reinforced PLA, and currently, some works on natural fiber reinforced PLA are reported [ 103 , 152 ]. The potential of FDM printed fiber reinforced composites formed by other bio-based polymers or bio-degradable biopolymers (as matrix) and natural fiber (as reinforcement) should be explored.…”
Section: Opportunities For Future Developmentsmentioning
confidence: 99%
“…[ 153 , 154 ]. Previously, most research focused on synthetic fiber reinforced PLA, and currently, some works on natural fiber reinforced PLA are reported [ 103 , 152 ]. The potential of FDM printed fiber reinforced composites formed by other bio-based polymers or bio-degradable biopolymers (as matrix) and natural fiber (as reinforcement) should be explored.…”
Section: Opportunities For Future Developmentsmentioning
confidence: 99%
“…Understanding the relationship between the sorption processes occurring in composites in contact with liquids, stress [ 16 ] and ORFB deformation kinetics as well as the reason for the loss of the elastic properties of polymer composites is important for various applications [ 16 , 17 , 18 ] and for the uninterrupted operation of offset printing machines [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, sheet metal is used as an additional material. Sheets are popular because of their low cost and good mechanical properties, but their disadvantage is that they increase the weight of the resulting sandwich material [ 3 , 4 , 5 , 6 ]. Natural or synthetic material can be used as the core material.…”
Section: Introductionmentioning
confidence: 99%
“…At low cyclic fatigue, destruction of the sample should not occur within 10 thousand repetitions [ 11 , 12 , 13 ]. It is commonly reported that the strength and service life of products is reduced at low stress values during cyclic fatigue of materials, especially when polymer-based materials are used [ 3 , 6 ]. Research indicates that cyclic fatigue causes an irreversible change before the maximum strength of materials is reached [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation